Mice develop obesity and lose myocardial metabolic flexibility months after exertional heat stroke - Jamal M. Alzahrani; Ashley J. Smuder; Bryce J. Gambino; Cristina Delgado; Michael T. Rua; Ryan N. Montalvo; Finleigh P. Fitton; Deborah A. Morse; Thomas L. Clanton (Communications Biology)
Abstract As global temperatures rise, heat-related chronic health disorders are predicted to become more prevalent. We tested whether a single exposure to acute heat illness, using a preclinical mouse model of exertional heat stroke (EHS), can induce late-emerging health disorders that progress into chronic disease. Following EHS, mice were followed for 3 months; after two weeks of recovery, half were placed on a Western diet to determine if previous EHS exposure amplifies the negative consequences of an atherogenic diet. When compared to sham exercise controls, EHS-exposed mice exhibit accelerated diet-induced obesity, develop low level cardiac hypertrophy, develop accelerated diet-induced liver steatosis, severe hypoproteinemia and a loss of metabolic flexibility in the myocardium. The latter is characterized by a shift towards predominant glucose metabolism and glycolysis. These results demonstrate that a single exposure to severe exertional heat illness can induce long-lasting and unexpected health consequences in mammals and increased vulnerability to secondary metabolic stressors.